IMPLEMENTASI SISTEM MONITORING BUS TRANS SEMARANG BERBASIS LORA (LONG RANGE) - Tasdik Darmana; Fadila Annas; Ariman . (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT Trans Semarang buses as transportation used by residents the city of Semarang often experience delays at one corridor stop so that passenger waiting times are quite long, so monitoring is needed on each bus. LoRa with long-distance communication capabilities without an internet signal with low power over a wide area, so it can be used to monitor the position and speed of the Trans Semarang bus for efficient passenger waiting time. The tool used to monitor Trans Semarang bus consists of a transmitter section as a data sender and a receiver as a data receiver with 915 MHz LoRa communication media and there is a buzzer as a bus speed warning and an emergency button when the bus has problems on the road. The test results from this study are the device can send and receive data with the furthest distance of 2200 meters with a maximum speed that can be measured is 46 km/hour, then it can give speed limit warnings and bus emergency warnings. Keywords : LoRa 915 MHz, Trans Semarang Bus, Distance, Speed